Flow Diversion versus Traditional Endovascular Coiling Therapy: Design of the Prospective LARGE Aneurysm Randomized Trial - Turk, A.S. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: The goal of aneurysm treatment is occlusion of an aneurysm without morbidity or mortality. Using well-established, traditional endovascular techniques, this is generally achievable with a high level of safety and efficacy. These techniques involve either constructive treatment of the aneurysm (coils with or without an intravascular stent) or deconstruction (coil occlusion) of the aneurysm and the parent artery. While established as safe and efficacious, the constructive treatment of large and giant aneurysms with coils has typically been associated with relatively lower rates of complete occlusion and higher rates of recurrence. Parent artery deconstruction, though immediately efficacious in achieving complete and durable occlusion, does require occlusion of a major intracranial blood vessel and is associated with risk of stroke. MATERIALS AND METHODS: Flow diversion represents a new technology that can be used to constructively treat large and giant aneurysms. Once excluded successfully, the vessel reconstruction and aneurysm occlusion appears durable. The ability to definitively reconstruct cerebral blood vessels is an attractive approach to these large and giant complex aneurysms and allows the treatment of some aneurysms which were previously not amenable to other therapies. By comparison, conventional coiling techniques have traditionally been used for endovascular treatment of large aneurysms. Large and giant aneurysms that are amenable to either flow diversion or traditional endovascular treatment will be randomized to either therapy with FDA (or appropriate regulatory body) approved devices. RESULTS: The trial is currently enrolling and results of the data are pending the completion of enrollment and follow-up. CONCLUSIONS: This paper details the trial design of the LARGE trial, a blinded, prospective randomized trial of large anterior circulation aneurysms amenable to either traditional endovascular treatments using coils or reconstruction with flow diverters.